Extracting risk-neutral probability distributions from option prices using trading volume as a filter - Dominique Y. Dupont (Institute for Advanced Studies (IHS), 2001)
This paper introduces a new technique to infer the risk-neutral probability distribution of an asset from the prices of options on this asset. The technique is based on using the trading volume of each option as a proxy of the informativeness of the option. Not requiring the implied probability distribution to recover exactly the market prices of the options allows us to weight each option by a function of its trading volume. As a result, we obtain implied probability distributions that are both smoother and should be more reflective of fundamentals.
Keywords: G13; G14; 330; implied risk-neutral probability distribution; implied-tree method; Optionspreistheorie; Theorie